If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(6x + -7) = 0 Reorder the terms: (5 + x)(6x + -7) = 0 Reorder the terms: (5 + x)(-7 + 6x) = 0 Multiply (5 + x) * (-7 + 6x) (5(-7 + 6x) + x(-7 + 6x)) = 0 ((-7 * 5 + 6x * 5) + x(-7 + 6x)) = 0 ((-35 + 30x) + x(-7 + 6x)) = 0 (-35 + 30x + (-7 * x + 6x * x)) = 0 (-35 + 30x + (-7x + 6x2)) = 0 Combine like terms: 30x + -7x = 23x (-35 + 23x + 6x2) = 0 Solving -35 + 23x + 6x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -1x)(7 + -6x) = 0Subproblem 1
Set the factor '(-5 + -1x)' equal to zero and attempt to solve: Simplifying -5 + -1x = 0 Solving -5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 0 + 5 -1x = 0 + 5 Combine like terms: 0 + 5 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5Subproblem 2
Set the factor '(7 + -6x)' equal to zero and attempt to solve: Simplifying 7 + -6x = 0 Solving 7 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -6x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -6x = 0 + -7 -6x = 0 + -7 Combine like terms: 0 + -7 = -7 -6x = -7 Divide each side by '-6'. x = 1.166666667 Simplifying x = 1.166666667Solution
x = {-5, 1.166666667}
| 7(7x+6)-x=8(4+6x) | | 3k=2k-16 | | f(x)=(2x-1)(x+2)(x+3) | | (7x-1)(x-7)=0 | | -4(w-7)=-7w+19 | | 18=3(j-13) | | 2(4+7x)=-3(1-4x)+5 | | 2u+38=7(u-1) | | r-10/3=3 | | .42/7.00=x/100 | | (2x-1)(2x+7)=0 | | 3(p-13)+4=13 | | x^5-ax^2-ax+1=0 | | -6(8v-4)=6(6v+4) | | n+9=4v-6 | | 8y=3x-12 | | 2(1+8x)=4(4x+8) | | ax+y=bx+K | | -6(4x-6)=-18-6x | | (3i+8)(6i-7)= | | 4(x+5)-2x+2=3(2x-4)+x+9 | | x+90+70=180 | | -3(4v+8)=-18-6v | | H(t)=-16t^2+342+1000 | | 4/2x-2916=1/9 | | x^2+6x+12=2x-1 | | 30=-w+247 | | -7b+28=-8(5+3b) | | 4(32-2b)=144 | | 242-u=133 | | 1+7x=4x+16 | | 3(2x+5)=(3x+3) |